Rekonstruksi Akad Hutang Yang Diansurasikan Perspektif Sad Al-Dhari'ah - Bakhrul Huda (MASADIR: Jurnal Hukum Islam, 2021)
The Debt Contract (Qard) is originally quite simple, where the debtor (muqtariá¸) is the one who really needs it to fulfill his primary needs. With the presence of banking today, muqtariá¸ is no longer a person who really needs to fulfill their primary needs, but secondary and even tertiary needs are served by the bank (muqri) with collateral from muqtari customers or insurance. This article wants to reconstruct how the practice of insured debt from Sad al-DharÄi' perspective. With library research model and normative approach, where the data used is secondary data. As a result, the insured debt is categorized as a hybrid contract if it is analyzed by Sad al-DharÄi' there are benefits and harms. However, as long as the debt is far from usurious and the insurance is included in the category that the majority of scholars allow it, it is not a problem to become a hybrid contract. But if you choose to apply a minor opinion, then there is no problem with the insured debt contract.